Revision of the genus Istrianis Meyrick, 1918 (Lepidoptera, Gelechiidae) with special regard to the Palaearctic region - Bidzilya, Oleksiy; Karsholt, Ole (Zootaxa, 2015)
Twenty-one species of the genus Istrianis are recognized as valid in the world fauna, 11 of which are described as new: I. pseudomyricariella sp. nov. (Greece, Kyrgyzstan, Tadzhikistan), I. nilssoni sp. nov. (Greece), I. kravchenkoi sp. nov. (Palestine), I. sattleri sp. nov. (Pakistan), I. armatus sp. nov. (Yemen), I. lvovskyi sp. nov. (Mongolia), I. sruogai sp. nov. (Turkmenistan, Tadzhikistan), I. piskunovi sp. nov. (Ukraine), I. falkovitshi sp. nov. (Turkmenistan), I. kyrgyzsquamella sp. nov. (Kazakhstan, Kyrgyzstan), I. yemeniasquamella sp. nov. (Yemen). Teleia myricariella var. arenicolella Caradja, 1920 is re-called from synonymy of I. myricariella (Frey, 1870) and considered as a valid species: Istrianis arenicolella (Caradja, 1920) sp. rev. One new synonym is established: Teleia amilcarella Lucas, 1933 syn. nov. of I. arenicolella. One new combination is proposed: I. steganotricha (Meyrick, 1935), comb. nov. (ex Telphusa). Redescriptions and identification keys for all the Palaearctic species and for two new species from Yemen are provided, accompanied by illustrations of the adults, and male and female genitalia.